Myopathology, a 14-Year Siriraj Experience: What have we learned? - Sangruchi, Tumtip; Liewluck, Teerin (Siriraj Medical Journal, 2003)
Neuromuscular laboratory, Department of Pathology Siriraj Hospital was established in 1989. Within fourteen years, 315 specimens from 304 patients were received. The patients’ age ranged from 22-week gestation to 76 years old. The ratio of males to female was 1.11:1. Muscular dystrophies comprised 26.63%, non-specific changes 25.66%, primary myopathies, including unclassified myopathy 13.82%, neurogenic muscle diseases 12.82% dysimmune and infectious myopathies 8.89%, mitochondrial myopathy 4.94% and others 7.24%. Summaries of our patients were described.